Gaussian approximation for Ising model. Variational approach - Yanishevsky, V.S. (Condensed Matter Physics, 2000)
A variant of a Gaussian approximation in Ising model of phase transition
is suggested. The method of functional integration with the application of
a variational method is put in the basis of the approach. The Hamiltonian
(the functional) is presented which in the method of functional integration
produces the known results of a two-tails approximation obtained by a diagram method. The application of a variational method eliminates a principal
demerit of the two-tails approximation – incorrect description of the phase
transition order. The results of numerical calculations for two and three-dimensional lattices are presented. Запропоновано варіант гаусового наближення в ізінгових моделях
фазових переходів. В основу підходу покладено метод функціонального інтегрування в поєднанні із варіаційним методом. Наведено
гамільтоніан (функціонал), що відтворює в методі функціонального
інтегрування відомі результати наближення двохвосток отримані діаграмним методом. Застосуванням варіаційного методу усувається
головний недолік наближення двохвосток – неправильний опис роду
фазового переходу. Наводяться чисельні розрахунки для дво- і тривимірної граток.